2016
DOI: 10.1002/ijc.30100
|View full text |Cite
|
Sign up to set email alerts
|

Development of ZMYM2‐FGFR1 driven AML in human CD34+ cells in immunocompromised mice

Abstract: Acute myelogenous leukemia (AML) has an overall poor survival rate and shows considerable molecular heterogeneity in its etiology. In the WHO classification there are >50 cytogenetic subgroups of AML, many showing highly specific chromosome translocations that lead to constitutive activation of individual kinases. In a rare stem cell leukemia/lymphoma syndrome, translocations involving 8p11 lead to constitutive activation of the fibroblast growth factor receptor 1 (FGFR1) kinase. This disorder shows myeloproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…Despite minor differences, such as the presence of eosinophilia in some cases, or a preference for the development of T‐lymphoma or B‐lymphoma between the subsets of common rearrangements, the BCR‐FGFR1 gene stands out in that this is typically a more aggressive disease. We have also seen this in our model systems where disease onset is disproportionately early amongst the mouse syngeneic models as well as in human xenograft models using transformed CD34+ stem cells . The BCR‐FGFR1 rearrangement is also distinct amongst the SCLL rearrangements in that the BCR component of the chimeric gene encodes for a serine‐threonine kinase which may modify and enhance the phenotypes generated as a result of its expression.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Despite minor differences, such as the presence of eosinophilia in some cases, or a preference for the development of T‐lymphoma or B‐lymphoma between the subsets of common rearrangements, the BCR‐FGFR1 gene stands out in that this is typically a more aggressive disease. We have also seen this in our model systems where disease onset is disproportionately early amongst the mouse syngeneic models as well as in human xenograft models using transformed CD34+ stem cells . The BCR‐FGFR1 rearrangement is also distinct amongst the SCLL rearrangements in that the BCR component of the chimeric gene encodes for a serine‐threonine kinase which may modify and enhance the phenotypes generated as a result of its expression.…”
Section: Discussionmentioning
confidence: 67%
“…Although we have defined two mechanisms of resistance to FGFR1 inhibitors, it is possible that other mechanisms may arise that will need alternative strategies to treat these resistant clones. Extensive molecular analyses of SCLL models in vivo and in vitro have suggested some potential targets, [13][14][15]25,30,41 such as FLT3, MYC and NOTCH1. Although AML is the primary consequence of constitutive activation of FGFR1 in SCLL, B-and T-cell lymphomas also develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because human leukemia/lymphomas associated with FGFR1 rearrangement is rare, we have developed several humanized mouse models engrafted with the FGFR1 fusion kinase-transduced human CD34+ progenitor cells in immunocompromised mice as described previously. 4 , 7 , 8 CD34+ progenitor cells transduced with either ZMYM2-FGFR1, 7 CNTRL-FGFR1, 4 or BCR-FGFR1, 8 developed acute myeloid leukemia (AML) with a human CD45+CD13+CD34+/CD38+ immunophenotype. Quantitative RT-PCR analysis showed that MYC is highly transcribed in cells from mouse spleens from all three models compared with either control pMIG3 transduced mouse splenocytes or healthy human PBMC ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to CpG methylation, downregulation of KLF4 is associated with deregulation of microRNAs such as miR‐10a and miR‐10b, and the transcriptional repression of KLF4 by CDX2 in AML is associated with inhibition of PPARγ signaling . Conversely, when human CD34 + cells are transduced with ZMYM2‐FGFR, the fusion protein product of the t(8;13)(p11;q12) chromosomal translocation found in myeloproliferative neoplasm, and transplanted into NSG mice, the mice display elevated KLF4, suggesting a potential oncogenic function . In contrast, AML patients with a low level of HDAC1, which is negatively correlated with KLF4 level, exhibit better prognosis .…”
Section: Role Of Klf4 In Leukemic Stem Cellsmentioning
confidence: 99%